Sintilimab combined with AVD for the treatment of composite Hodgkin lymphoma and follicular lymphoma: a case report and literature review - Ye, Huami; Huang, Linlin; Chen, Changqian; Huang, Shihua; Hu, Lianjie; Wang, Ling (Frontiers in Oncology, 2026)
Composite lymphoma has been rarely reported due to its low incidence. The treatment of composite lymphoma depends on the specific lymphoma subtypes involved. No standardized therapeutic regimen has been established. We tried to treat the patient with Sintilimab+AVD for composite Hodgkin lymphoma and follicular lymphoma, after which the patient was able to maintain a normal quality of life and achieved partial remission (PR). To the best of our knowledge, this is the first attempt to use the PD-1 inhibitor combined with the AVD regimen successfully for the treatment of composite Hodgkin lymphoma and follicular lymphoma.